(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The contraceptive method that is most in demand by the public is the injection type contraceptive method, even though the IUD and Implant are more effective. Cadres, Family Planning Field Officers, and Midwives are officers who directly carry out IEC on contraceptives for fertile aged couples. The poor quality of IEC will affect the receipt of information about IUD contraceptives and implants. Objective: The purpose of this study was to determine the implementation of IEC in the Family Planning Program in improving IUD and implants Methods: This study is a qualitative study with a case study design. The unit of analysis in this study is at the individual level. Research subjects for the qualitative study were 1 person from P3AP2KB Sleman Regency, namely the Head of IEC, 4 Family Planning Field Officers, 17 family planning cadres, and 4 PUS, 2 midwives in the Moyudan Health Center and Mlati Health Center. The sampling technique was done by using purposive sampling technique. Data analysis was performed by using explanation techniques (explanation building) Results: Cadres and Family Planning Field Officers do not use the media optimally and material presented is limited. The obstacles experienced by cadres in the Information and Education Communication process were not mastering the material and not having the skills to do IEC, while the obstacles experienced by Family Planning Field Officers were a lack of Human Resources and a double workload so they could not directly provide IEC to couples of childbearing age. Conclusion: The implementation of Information and Education Communication for Fertile Couples by Cadres and Family Planning Field Officers generally does not work properly. The impact is that many fertile aged couples do not use contraceptives. Keyword: Communication, Information, Education, Family Planning